Association of Single Nucleotide Polymorphisms (SNPS) to Black Spot Resistance in Roses - Yemer, Genet Kebede; Debener, Thomas; Linde, Marcus; Maiss, Edgar (Universitas Panji Sakti, 2024)
Rose black spot caused by Diplocarpon rosae is the most severe and global disease of garden roses. Breeding of disease resistant varieties is one of the most important goals of modern garden rose breeding. Single nucleotide polymorphisms (SNPs) are the most abundant type of polymorphism found in eukaryotic genomes. SNP markers can be used in a wide variety of applications, including association studies, genetic diversity analysis, and marker-assisted selection in plant breeding programs. The aim of this project was to analyze black spot resistance in a rose association panel through leaf inoculation assays with single isolate pathotypes as well as a field mixture of D. rosae isolates and to establish a relationship between resistance and the available SNP markers. In this study, 96 diverse cultivars of roses were evaluated phenotypically for resistance against black spot through artificial inoculations. 63000 SNPs that were developed in previous studies were used to genetically analyze the cultivars and find associations with resistance against black spot disease using mixed linear model in TASSEL 3.0. Differences in the phenotypic reaction to field mixture of isolates and the Ab13 single conidial isolate of this pathogen were observed between genotypes. One hundred and forty-nine SNPs were found to be significantly associated with resistance against field mixtures of black spot. For the Ab13 single isolate, only one significant SNP was found. These SNPs were mapped on the rose chromosomes, and found on chromosome one, three and four. These associated SNP and Rdr1 markers can be used for marker-assisted selection in breeding for black spot resistance in rose.